The Memoirs of Jacques Casanova de Seingalt, Vol. VI (of VI), "Spanish Passions" : The First Complete and Unabridged English Translation, Illustrated with Old Engravings - Casanova, Giacomo, 1725-1798; Machen, Arthur, 1863-1947 (Salt Lake City, UT : Project Gutenberg, 2012)
"The Memoirs of Jacques Casanova de Seingalt, Vol. VI (of VI), 'Spanish...'" is part of the autobiography written by Giacomo Casanova, an 18th-century Venetian adventurer. This volume forms part of the final installment of his sprawling 3,500-page life story, originally penned in French. The memoirs chronicle Casanova's remarkable adventures from birth through 1774, capturing the world of an educated European during the Enlightenment. Written during illness and polished for publication, these pages reveal an extraordinary life that captivated readers across centuries, despite early editions being heavily censored and mistranslated. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Histoire_de_ma_vie
Release date is 2012-03-29
Produced by David Widger
Keywords: Casanova, Giacomo, 1725-1798; Europe -- History -- 18th century -- Biography